A Novel Tube Insertion Technique for Glaucoma Drainage Device Implantation. Issue 2 (20th February 2023) - Mohite, Abhijit A.; Cheng, Mei-Ling; Sung, Velota C.T.
Abstract : Purpose: Early hypotony after non-valved glaucoma drainage device (GDD) implantation for complex glaucomatous eyes with labile aqueous production can lead to significant visual morbidity. We therefore sought to report the early postoperative outcomes of a novel surgical technique that allows atraumatic insertion of non-valved GDDs through a much smaller 25-gauge scleral track, to minimize entry site leakage and improve safety. Methods: Retrospective case series of 15 consecutive cases undergoing non-valved GDD insertion into the anterior chamber using a previously unreported technique. Results: All eyes underwent successful GDD insertion using our novel technique, with no intraoperative complications. The mean preoperative intraocular pressures (IOP), at day 1, week 1 and week 3 were 31.4, 22.4, 23.7, and 25.6 mm Hg, respectively. A statistically significant IOP reduction was achieved at day 1, week 1 and week 3 postoperatively ( P <0.05) without any observed leakage at the scleral entry site. One eye (6.7%) with complex panuveitic glaucoma developed early hypotony (5 mm Hg) with shallow choroidal detachments on day 1. This was successfully managed with 1 intracameral ophthalmic viscoelastic device injection given at the slit-lamp and no further intervention. Conclusions: This novel single needle-docking intraocular insertion manoeuvre is an easily adoptable technique to make GDD insertion through a smaller 25-gauge water-tight scleral track more efficient and less traumatic. The technique reduces scleral distortion and therefore improves surgical safety particularly in eyes with complex secondary glaucoma.